Hydrometeorological Observations by the Whaling Ship Slava-15 of the Antarctic Whaling Fleet in 1955-58 and Pelagic Hydrological Observations in 1950-51 and 1953-58 GG (Gidrometeorologicheskie Nablyudeniya na Kitoboinom Sudne 'Slava-15' Antarkticheskoi Kitoboinoi Flotilii v 1955-58 GG. i Glubokovodnye Gidrologicheskie Nablyudeniya v 1950-51 i 1953-58 GG) - Ivanov,A. P.; Kirillov,I. F.; Rybnikov,A. A.; Sirotov,K. M. (1962)
On the basis of observations carried out from aboard whaling ships, the main properties of wave regime in the area of Buve (Bouvet) Island have been elucidated. The information on maximum heights of wind waves in Antarctic waters is furnished and recommendations for computations of wave heights at various wind speeds are given. Tables permitting the forecasting of the time of wave development and decay in approximation are listed. The significance of wind waves for commercial vessels is pointed out and examples showing the effect of strom waves on the AKF vessel Slava are given. (Author) Trans. of Gosudarstvennyi Okeanograficheskii Institut. Trudy (USSR) v58 p252-267 1960, by M. Slessers.